Missing growth measurement in Germany - Sven Schreiber; Vanessa Schmidt (Freie Universität Berlin, School of Business & Economics, 2021)
Using detailed establishment-level micro data, this paper analyzes for the German case the hypothesis by Aghion, Bergeaud, Boppart, Klenow, and Li (2019), stating that officially published figures for real output growth would be systematically understated. The effect rests on overstated inflation estimates due to imputed prices for disappearing goods and services varieties, where measurable plant entry and exit dynamics play a crucial rule. Our main results regarding understated real output growth lie in the range of 0:39 to 0:54 average annual percentage points for 1998-2016, which is quite closely in line with existing findings for France, the USA, and Japan (in different periods). We also find that services sectors appear most affected, and that the effect in East Germany is somewhat larger. We investigate different market share proxies, provide additional robustness analysis and also discuss limitations of the approach.
urn:nbn:de:kobv:188-refubium-29825-3
Keywords: E31; O47; 330; creative destruction; price imputation; inflation measurement